Akuntansi Syariah: Suatu Pengantar Aliran Pemikiran - Rizky Iman Perkasa Wardoyo Putra (Movere Journal, 2020)
The unrest and change of Indonesian society towards the conventional economic practice system made the results that became the basis of Islamic economic development in Indonesia with the establishment of Bank Muamalat Indonesia in 1991 and operated in 1992. In that journey, business entities that carry out sharia practices in the financial statements require recording with also use methods based on Islamic principles. The practice of recording financial statements of sharia entities uses the method of recording the trust in sharia accounting flows that have been issued. This type of research uses qualitative methods by conducting a literature study of secondary data, where secondary data is data obtained from studies that have been carried out research and other sources of reference.